Interpretive structural modelling of organizational innovation factors: An emerging market perspective - Mohammad Alawamleh; Arwa Al-Twal; Leen Lahlouh; Raghad Ousama Jame (Journal of Open Innovation: Technology, Market and Complexity, 2023)
This research aims to identify key factors in organizational innovation and their interrelationships using Interpretive Structural Modelling (ISM). An interpretive review of related literature was utilized to develop a multi-level structured model ISM with the help of MICMAC analysis to determine the driving and dependence power of each identified factor. 11 factors were identified and the extent to which they influence organizational innovation was explored. Diversity, empowerment, and Training & Development are the strongest driving forces (independent factors), whereas innovation and organizational culture had the lowest driving power and highest dependence (dependent factors). This study provides a foundation for further research development and managerial practice to emphasize major factors driving organizational innovation. However, the application of ISM model incorporates subjective judgments that may affect the results. This research extends beyond existing literature in integrating a plethora of factors influencing and inhibiting innovation in organizations, and in providing an explicit and comprehensive view of these factors’ interrelationships and mutual primary effects, with implications for promoting employee creativity and thus organizational innovation.